Therapeutic potential of the chemical composition of Dendrobium nobile Lindl. - Fan, Chenxi; Sun, Xin; Wang, Xin; Yu, Hongsong (Frontiers in Pharmacology, 2023)
Dendrobium nobile Lindl belongs to the genus dendrobium of the orchid family and is a valuable herbal medicinal material. The information in this paper has been collected from the scientific literature databases including PubMed, Google Scholar, Web of Science, SciFinder, China National Knowledge Infrastructure, published books, Ph.D. and M.S. dissertations systematically in recent twenty years. " Dendrobium nobile Lindl ", " chemical composition ", " pharmacological activities ", and "diseases" were used as search terms to screen the literature. The collected chemical compositions are classified and summarized according to their different chemical structures, and the clinical disease treatment effects of Dendrobium nobile Lindl are classified and summarized based on their pharmacological activities and different experimental disease models. Recent studies have revealed that Dendrobium nobile Lindl contains chemical components such as alkaloids, bibenzyls, sesquiterpenes, phenanthrenes, and polysaccharides, and that its pharmacological activities are closely related to the chemical components, with pharmacological activities such as anti-tumor, anti-aging, immune enhancement, hypoglycemic, anti-cataract. Currently, researchers are conducting extensive and detailed studies on Dendrobium nobile Lindl and conducting research experiments on its chemical constituents in the treatment of various clinical diseases. Therefore, the purpose of this paper is to review the chemical composition of Dendrobium nobile Lindl and its experimental studies in the treatment of diseases, and to provide a scientific reference for the future application of Dendrobium nobile Lindl in the treatment of diseases.